1973
DOI: 10.1001/archneur.1973.00490250071008
|View full text |Cite
|
Sign up to set email alerts
|

Axon Outgrowth Enhanced by a Previous Nerve Injury

Abstract: In the sciatic nerve of adult mice, the rate of axonal elongation following nerve excision was 27% faster than normal if the nerve had been crushed two weeks before the excision.(29: [53][54][55] 1973)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
2

Year Published

1985
1985
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(133 citation statements)
references
References 9 publications
4
127
0
2
Order By: Relevance
“…Preconditioning dramatically ramps up regenerative neurite outgrowth, a mechanism that involves, among others, heightened intracellular cAMP and increased expression of many regenerationassociated genes, including ␤III tubulin, GAP43/B50, and others (McQuarrie and Grafstein, 1973;McQuarrie et al, 1977;Forman et al, 1980;Oblinger and Lasek, 1984;Schreyer and Skene, 1991). Our prediction was that preconditioning would suppress PTEN activity, so that little added benefit would accrue from its inhibition.…”
Section: Inhibition Of Pten At the Protein Level In Vitro Increases Nmentioning
confidence: 91%
“…Preconditioning dramatically ramps up regenerative neurite outgrowth, a mechanism that involves, among others, heightened intracellular cAMP and increased expression of many regenerationassociated genes, including ␤III tubulin, GAP43/B50, and others (McQuarrie and Grafstein, 1973;McQuarrie et al, 1977;Forman et al, 1980;Oblinger and Lasek, 1984;Schreyer and Skene, 1991). Our prediction was that preconditioning would suppress PTEN activity, so that little added benefit would accrue from its inhibition.…”
Section: Inhibition Of Pten At the Protein Level In Vitro Increases Nmentioning
confidence: 91%
“…Studies of axonal regeneration in the sciatic nerve have shown that a conditioning lesion of the tibial nerve (a branch of the sciatic nerve) made 2 weeks before a sciatic nerve injury causes a significant increase in axon outgrowth. 40,41 Further work has shown that regeneration of dorsal root ganglion central processes into a peripheral nerve graft and regeneration of dorsal column fibers into a spinal cord lesion site is significantly improved by performing a peripheral nerve lesion. Thus, a preconditioning nerve lesion seems to increase the intrinsic regenerative ability of central axons by enhancing endogenous repair processes, such as elevation of intracellular cyclic adenosine monophosphate that allow axons to overcome myelin inhibition or by promoting of neuronal survival through attenuation of several injury-inducing mechanisms such as excitotoxicity, ion/pH imbalance, oxidative stress, metabolic dysfunction, and inflammation.…”
Section: -26mentioning
confidence: 99%
“…One of the best characterized examples of cytokine involvement in sympathetic neuroanatomical plasticity is their participation in neurite outgrowth following a conditioning lesion, such as axotomy (McQuarrie and Grafstein, 1973;McQuarrie et al, 1978). The conditioning lesion enhances the expression of cytokines of the gp130 family, which includes leukemia inhibitory factor, IL-6, IL-11, and oncostatin M, in tissues innervated by the axotomized sympathetic neurons and in the sympathetic neurons themselves (Hyatt Sachs et al, 2010).…”
Section: Comparison With the Conditioning Lesion Effectmentioning
confidence: 99%